Human resource practices and innovativeness: A conceptual paper - Nadia Nasser Abdulla Khamis Al Junaibi; Kamarudin, Mohd Fauzi (JPB Review, 2023)
Purpose: The purpose of this study is to review and produce a set of propositions about the function of human resource practises and innovativeness in a business environment. Implications of research: Growing worldwide rivalry, extremely unpredictable markets, and even greater customer expectations have resulted as a result of the globalisation of the world, making it important for enterprises to be open to the possibility of innovation. Findings: According to the findings of this research, a paradigm for understanding the relationship between human resource practises and innovativeness, as well as the moderating effect of innovation capability, is proposed. Originality/Value: This document contains a series of propositions that constitute an empirically driven research agenda, as well as descriptions of the correlations between the focus variables that are given to improve the understanding of the audience in a business setting.